L’art rupestre de la Cueva de Cristóbal (Puna de Jujuy, Argentine): Nouveaux éléments - Gerónimo, Aldo Agustín; Hocsman, Salomón
New evidence of rock art at the site Cueva de Cristóbal in the La Matadería Massif, between Sierras de Aguilar and Alta, Jujuy Puna (Argentina) (Fig. 1) are presented in this work. This art belongs to the Stylistic Group B (GEB) identified by Aschero (1979) and Aschero et al. (1991) for the nearby Quebrada de Inca Cueva. It includes figurative and non-figurative motifs. Among the first are isolated, grouped or articulated anthropomorphic figures, camelids and undetermined zoomorphs, while the second shows dots, pectiniform pictures and segmented traces, wide, isolated dashes and dashed and wavy lines (Aschero et al. 1991). Anthropomorphs are outstanding in this stylistic group since there are no previous correlates in the area. Nous présentons les nouvelles découvertes d’art rupestre à la Cueva de Cristóbal, massif de La Matadería, entre les Sierras de Aguilar et Alta, Puna de Jujuy (Argentine) (fig. 1). Cet art appartient au Groupe Stylistique B (GEB) identifié par Aschero (1979) et Aschero et al. (1991) pour la grotte proche Quebrada de Inca Cueva. Il s’agit de motifs figuratifs et non-figuratifs. Les premiers sont isolés, groupés ou associés à des anthropomorphes, des camélidés et des zoomorphes indéterminés, tandis que les seconds sont constitués de points, de pectiniformes, de segments, larges, tirets et pointillés isolés et lignes ondulées (Aschero et al., 1991). Les anthropomorphes sont remarquables dans ce groupe stylistique, puisque uniques dans la région. Fil: Gerónimo, Aldo Agustín. Universidad Nacional de Tucumán. Facultad de Ciencias Naturales e Instituto Miguel Lillo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Hocsman, Salomón. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Instituto Superior de Estudios Sociales. Universidad Nacional de Tucumán. Instituto Superior de Estudios Sociales; Argentina